Dynamic modeling of the CO2 emissions behavior by fossil fuel combustion during the land sequence preparation and pre-harvest activities in a sugar cane crop (2017)
(Eng) This paper presents the results of a study pursuing the evaluation of the CO2 emissions behavior by fossil fuel combustion from the agricultural equipment used during the land sequence preparation and pre-harvest activities in a sugarcane crop corresponding to a sugar mill of the Valle del Cauca state, as a local study case. A simulation model from the system dynamics point of view was developed as a research methodology. The main results reveal that the land sequence preparation activities represent 73% of the total CO2 emissions in respect of the pre-harvest activities considered in this study, like the fertilization and the weed control. Through some sensitivity analyses by considering a complete conversion from commercial to organic area for the next 25 years, it is not possible to observe significant changes in the cumulative levels of CO2 emissions (decrease of 2.3%). However, changing the land sequence preparation from “conventional” to “light 3”, these emissions reduced up to 22.65%. Thus, we obtained a carbon footprint of 70,103.8 t of CO2-eq and a level of cost savings of 64% compared to the diesel fuel. Finally, this research shows that the adoption of specific agricultural practices by agro-ecological zones represents an opportunity to reduce the long-term CO2 emissions.